PENGEMBANGAN LEMBAR KERJA MAHASISWA BERBANTUAN APLIKASI PhET PADA MATERI HUKUM ARCHIMEDES - aisyah aisyah; Evitamala Siregar; Rizki Fadilah (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2026)
The research is motivated by the existence of student misconception in science material, especially in physics which is abstract, low understanding of core concepts, and limited instrument that can facilitate student indepentdent exploration. The porpuse of this research is to develop a Student Worksheet assisted by Phet Interactive Simulation application that is valid, practical, and effective. The research method used is Research and Development (RD) with the ADDIE development model. The research instrument include expert validation by media expert and related materials, student response questionnaires, and learning outcome test result through pre-post tests. The expected research results show that the development of Student Worksheet assisted by PhET Interactive Simulation is in the very valid, prscticsl, effetive category, and can significantly improve conceptual understanding as shown by an increase in student learning outcomes. The integration of PhET Interactive Simulation not only provides learning flexibility but also improves students’ science process skills.